Enhancing Religious Tourist Satisfaction: The Role of Service Quality and Facilities at Bubohu, Gorontalo - Perdana, Dian Adi; Abdul Rahim Hamzah; Hendri Ajihuda; Abdul Charis; Saerozi (ECOTAS, 2025)
Bubohu religious tourism is located in the coastal area of ??Bongo Village and is close to other tours, namely the Walima Emas Mosque and Dulanga Beach. This tour is close to hilly areas and the sea which is the main attraction. This halal tourism industry has an attraction for both domestic and foreign people, so that from time to time it continues to grow. This privately managed halal tourism continues to improve the quality of services and facilities to provide the best for visitors. This study aims to examine and analyze the effect of service quality and facilities on visitor satisfaction of religious tourism